Retarder for high-temperature-resistant high-strength cement paste and preparation method thereof

By using a combination of five-membered copolymer retarder with sodium borate and sodium tripolyphosphate, a retarder for high-temperature and high-strength cement slurry was prepared, which solved the problem of insufficient resistance to high-temperature at high temperatures, and achieved good settlement stability and extended thickening time of cement slurry.

CN119528472AActive Publication Date: 2025-02-28CHINA NAT PETROLEUM CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311093667.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The existing retarders lack the ability to resist high temperatures at high temperatures, resulting in poor high-temperature settlement stability of cement slurry and poor compatibility, affecting the cementing quality.

Method used

Using a five-metal copolymer retarder, acrylic acid, sodium styrene sulfonate, vinylpyrrolidone and phosphate acrylic acid, combined with sodium borate and sodium tripolyphosphate, chelating reaction was prepared to prepare a retarder for anti-high temperature and high-strength cement slurry by synthesizing the 2-acrylamide 2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, and phosphate acrylic acid, combined with sodium borate and sodium tripolyphosphate, and a chelating reaction was carried out.

Benefits of technology

It significantly extends the thickening time of the cement slurry, maintains good settlement stability, and solves the problem of poor settlement stability of the cement slurry caused by retarder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of retarders for well cementation, in particular to a retarder for high-temperature-resistant and high-strength cement paste and a preparation method of the retarder for the high-temperature-resistant and high-strength cement paste. The quinary copolymer retarder is prepared from 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid sodium p-styrenesulfonate, vinyl pyrrolidone and acrylic acid phosphate. The quinary copolymer retarder is prepared by the following steps: adding the quinary copolymer retarder, sodium borate and sodium tripolyphosphate into water, uniformly mixing, and carrying out chelation reaction. The retarder for the high-temperature-resistant and high-strength cement paste can obviously prolong the thickening time of the cement paste under high-temperature and high-pressure conditions, can also enable the cement paste to keep good sedimentation stability, and solves the problem that the existing retarder easily causes poor high-temperature sedimentation stability of the cement paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cementing retarders, in particular to a retarder for high-temperature resistant and high-strength cement slurry and a preparation method thereof. Background Art

[0002] To ensure safe cementing operations in ultra-deep wells at ultra-high temperatures, sufficient high-temperature retarders must be added to the cement slurry to adjust the thickening time to meet safe construction requirements. However, the long primary cementing section in ultra-deep wells, requiring large amounts of retarder, leads to a large temperature difference between the top and bottom of the cement slurry. This can easily lead to excessive retardation at the top of the slurry, posing a serious safety risk to subsequent operations.

[0003] Retarders are one of the three main ingredients in cementing slurries. Cementing ultra-deep wells in long, single-stage cementing sections faces the technical challenge of addressing the wide temperature range of 90°C to 230°C and a large temperature gradient of 140°C. High-temperature retarders used by foreign oil companies are expensive and cannot be used alone. They must be used in conjunction with other admixtures from the manufacturer, requiring high capital requirements and a long procurement cycle. Most domestic retarders lack the ability to withstand temperatures exceeding 200°C. They degrade at high temperatures, causing molecular chain scission, resulting in poor high-temperature stability of the cement slurry, poor compatibility with other cement slurry admixtures, and difficulty controlling the thickening time, leading to suboptimal cementing quality. A retarder for high-temperature-resistant, high-strength cement slurries with large temperature gradients over long cementing sections has become a bottleneck in the development of cement slurry technology for ultra-deep well cementing.

[0004] Currently, retarders used in China generally lack high-temperature resistance, with a temperature tolerance of no more than 200°C. They exhibit strong dispersion under high-temperature conditions and poor compatibility with other admixtures, posing serious safety risks to cementing operations. For example, lignin sulfonate retarders are only suitable up to 130°C. Carboxylic acid and its salts, such as the widely used tartaric acid, gluconic acid, and glucoheptonic acid, are also only suitable up to 150°C. Tartaric acid is prone to excessive retardation when bottomhole temperatures fall below 93°C. Boric acid or its salts, commonly used inorganic compounds, can compromise the effectiveness of polyamine and cellulose fluid loss additives when used with them, resulting in poor compatibility. Polymer retarders, such as 2-acrylamido-2-methylpropanesulfonic acid (AMPS) copolymer, can be overdosed, resulting in core formation during thickening experiments and a limited temperature range.

[0005] Domestic scholars have achieved certain results in the research of polymer high-temperature retarders. For example, Peng Zhigang, Xu Zunjian, Feng Qian and others used phosphorus-containing compounds as the main raw materials and hydroxyethyl acrylate, vinyl sulfonate and acrylic acid phosphate as polymerization monomers in a ratio of 4:2:1 to develop a polymer oil well cement retarder with a temperature resistance greater than 170°C but not exceeding 200°C; Qi Zhigang and others used itaconic acid (IA) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) as monomers to synthesize a binary copolymer retarder with a suitable operating temperature range of 120°C to 180°C; Sun Yongcai, Wang Xuguang and others used AMPS as the main structural unit and copolymerized it with two other ethylene monomers to prepare a high-temperature retarder DHTR400 with a maximum temperature resistance of 200°C. Research on the development of the top strength of cement slurry with large temperature differences is needed.

[0006] In view of the problems and defects of conventional retarders and polymer anti-high temperature retarders in terms of high temperature resistance and retarding ability, high temperature stability, compatibility and strength development of the top of the long sealing section, it is urgently necessary to develop new polymer anti-high temperature retarders through synthetic material optimization, grafting and modification to improve the working form and adsorption capacity of the retarder functional groups, optimize the retarding effect under high and low temperature conditions, and solve the difficult problems of weak high temperature resistance and slow strength development of the return surface of cement slurry in the long sealing section of ultra-deep wells. Summary of the Invention

[0007] The present invention provides a retarder for high-temperature resistant and high-strength cement slurry and a preparation method thereof, which overcomes the deficiencies of the above-mentioned prior art and can effectively solve the problem that the existing retarder easily causes poor high-temperature sedimentation stability of the cement slurry.

[0008] One of the technical solutions of the present invention is achieved through the following measures: a retarder for high-temperature resistant and high-strength cement slurry, the raw materials of which include a five-component copolymer retarder, sodium borate and sodium tripolyphosphate in a mass ratio of 10: (1 to 2): (0.6 to 1.1), and the raw materials of the five-component copolymer retarder include, by weight, 25 to 35 parts of 2-acrylamido-2-methylpropanesulfonic acid, 20 to 30 parts of acrylic acid, 20 to 30 parts of sodium styrenesulfonate, 5 to 8 parts of vinyl pyrrolidone and 7 to 10 parts of acrylic acid phosphate.

[0009] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: The above-mentioned retarder for high-temperature resistant and high-strength cement slurry is obtained by the following method: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution until it is completely dissolved, adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and obtaining a viscous liquid after a polymerization reaction occurs; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and perform a chelation reaction to obtain a viscous solution. Purify, dry and crush the viscous solution again, and dissolve it in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry.

[0010] In the above step S1, the mass concentration of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone and acrylic acid phosphate) in the mixed solution is 12% to 18%.

[0011] In the above step S1, the pH of the mixed solution is adjusted to 4 to 8 by using a sodium hydroxide solution with a mass concentration of 8% to 12%.

[0012] In the above step S2, the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of (1 to 1.5):1, and the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 3% to 5%.

[0013] In the above step S2, the amount of the initiator solution added is 12% to 40% by weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution.

[0014] In the above step S2, the stirring temperature is 30°C to 50°C, and the polymerization reaction time is 5h to 8h. In step S4, the chelation reaction is performed at a temperature of 45°C to 70°C, and the time is 4h to 6h.

[0015] In the above step S3, the mass concentration of the solutes (pentapolymer retarder, sodium borate and sodium tripolyphosphate) in the retarder for high-temperature resistant and high-strength cement slurry is 30% to 45%.

[0016] The second technical solution of the present invention is achieved by the following measures: a method for preparing a retarder for high-temperature resistant and high-strength cement slurry is carried out as follows: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution until it is completely dissolved, adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and obtaining a viscous liquid after a polymerization reaction occurs; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and perform a chelation reaction to obtain a viscous solution. Purify, dry and crush the viscous solution again, and dissolve it in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry.

[0017] The retarder for high-temperature resistant and high-strength cement slurry of the present invention can not only significantly prolong the thickening time of cement slurry under high temperature and high pressure conditions, but also enable the cement slurry to maintain good sedimentation stability, thereby solving the problem that existing retarders easily cause poor high-temperature sedimentation stability of cement slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The graph is a temperature and thickening time curve of cement slurry prepared using the retarder for high-temperature resistant and high-strength cement slurry prepared in Examples 12 to 14 of the present invention as raw materials; Figure 2 This is a thickening experimental curve diagram of the retarder for high-temperature resistant and high-strength cement slurry prepared in Example 13 of the present invention at 220°C. DETAILED DESCRIPTION

[0019] The present invention is not limited to the following embodiments, and specific implementation methods can be determined based on the technical solutions of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals commonly known in the prior art; unless otherwise specified, the percentages in the present invention are all percentages by mass; unless otherwise specified, the solutions in the present invention are all aqueous solutions with water as the solvent, for example, hydrochloric acid solution is an aqueous hydrochloric acid solution; normal temperature and room temperature in the present invention generally refer to temperatures between 15°C and 25°C, and are generally defined as 25°C.

[0020] The present invention will be further described below in conjunction with the embodiments: Example 1: The retarder for high-temperature resistant and high-strength cement slurry comprises raw materials including a five-component copolymer retarder, sodium borate and sodium tripolyphosphate in a mass ratio of 10:(1 to 2):(0.6 to 1.1). The raw materials of the five-component copolymer retarder include, by weight, 25 to 35 parts of 2-acrylamido-2-methylpropanesulfonic acid, 20 to 30 parts of acrylic acid, 20 to 30 parts of sodium styrenesulfonate, 5 to 8 parts of vinyl pyrrolidone and 7 to 10 parts of acrylic acid phosphate.

[0021] The retarder for high-temperature-resistant, high-strength cement slurry disclosed herein not only significantly prolongs the thickening time of the cement slurry under high-temperature and high-pressure conditions, but also maintains excellent settling stability. This is primarily due to the incorporation of the five-membered heterocyclic lactam compound, N-vinylpyrrolidone, into the monomer. This monomer forms stable intermolecular and intramolecular association structures, giving the retarder its temperature-sensitive properties, making it more adaptable to a wide range of cementing requirements. When the temperature is low, the hydration effect of the polar groups in the molecular chain is stronger than the chain hydrophobic effect, and the pentapolymer retarder is water-soluble. As the temperature rises, its hydration effect weakens, resulting in a decrease in viscosity and a suitable initial consistency. When the temperature is high, as the temperature rises, the degree of hydration of the molecular chain weakens, and the association effect of the hydrophobic groups in the molecule is significantly enhanced. In addition, due to the high SSS content in the pentapolymer retarder molecules, the strong hydrophilicity of the pentapolymer retarder molecular chain is guaranteed, so that the hydrophobic associating phase is maintained in a microscopic phase separation state without sedimentation, resulting in an increase in the hydrodynamic volume of the pentapolymer retarder molecules and an increase in the solution viscosity, that is, it exhibits good thickening properties, so that the retarder for high-temperature resistant and high-strength cement slurry prepared using the pentapolymer retarder prepared by the present invention as a raw material has excellent sedimentation stability under high temperature and high pressure.

[0022] In the present invention, the molecular weight of the pentapolymer retarder is between 12,000 and 38,000 and is easily soluble in water.

[0023] Example 2: As an optimization of the above example, the retarder for high-temperature resistant and high-strength cement slurry is obtained by the following method: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution until it is completely dissolved, adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and obtaining a viscous liquid after a polymerization reaction occurs; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and perform a chelation reaction to obtain a viscous solution. Purify, dry and crush the viscous solution again, and dissolve it in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry.

[0024] Example 3: As an optimization of the above example, in step S1, the mass concentration of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone and acrylic acid phosphate) in the mixed solution is 12% to 18%.

[0025] Example 4: As an optimization of the above example, in step S1, the pH of the mixed solution is adjusted to 4 to 8 by using a sodium hydroxide solution with a mass concentration of 8% to 12%.

[0026] Example 5: As an optimization of the above example, in step S2, the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of (1 to 1.5):1, and the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 3% to 5%.

[0027] In the present invention, the initiator solution is a mixture of ammonium persulfate and potassium bisulfite, which can maintain a good initiation effect at a relatively low temperature, with an effective ingredient conversion rate of 50% to 70%, and high efficiency. During the polymerization reaction, the initiator should be added as evenly and slowly as possible to prevent the polymerization reaction from being too intense and causing the reaction monomers to explode.

[0028] Example 6: As an optimization of the above example, in step S2, the amount of the initiator solution added is 12% to 40% by weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone and acrylic acid phosphate) in the mixed solution.

[0029] Example 7: As an optimization of the above example, in step S2, the stirring temperature is 30°C to 50°C, and the polymerization reaction time is 5h to 8h. In step S4, the chelation reaction temperature is 45°C to 70°C, and the time is 4h to 6h.

[0030] Example 8: As an optimization of the above example, in step S3, the mass concentration of the solute (pentapolymer retarder, sodium borate and sodium tripolyphosphate) in the retarder for high-temperature resistant and high-strength cement slurry is 30% to 45%.

[0031] In the present invention, the design idea of ​​the pentapolymer retarder is to appropriately increase the molecular chain length and molecular side chain rigidity, enhance the thermal stability of the main chain, improve the side chain rigidity, and maintain a relative balance between high temperature shear thinning and viscosity increase.

[0032] In the five-component copolymer retarder, the main chain is based on 2-acrylamido-2-methylpropanesulfonic acid, a functional group monomer containing a sulfonic acid group. At the same time, a functional group monomer sodium styrene sulfonate monomer is introduced into the main chain to enhance the rigidity of the molecular chain and steric hindrance, thereby enhancing the ability to resist high temperature and prevent sedimentation. In addition, a strongly adsorbable carboxylic acid group monomer acrylic acid is introduced to enhance the adsorption of cement particles under high temperature conditions, thereby ensuring the high-temperature retarding effect.

[0033] A five-membered heterocyclic lactam compound, N-vinylpyrrolidone, is grafted onto one end of the main chain, creating a stable molecular association structure and enhancing temperature sensitivity. At lower temperatures, the molecular chains aggregate, preventing the retarder molecules from expanding, significantly weakening their adsorption capacity to cement particles and promoting their hydration. At higher temperatures, the molecular side chains expand, significantly enhancing their adsorption to cement particles and effectively delaying the thickening time, thereby reducing the temperature sensitivity of the retarder for high-temperature-resistant, high-strength cement slurry.

[0034] The introduction of an acrylic acid phosphate monomer at the other end of the main chain enhances the rigidity of the main and side chains, widening the temperature resistance range. The ester group hydrolyzes slowly at high temperatures, participating in chelation to form new chelate groups, which then adsorb on the cement particle surface, further inhibiting cement hydration. This increases the temperature resistance of the pentapolymer retarder and reduces its temperature sensitivity. Ultimately, the pentapolymer retarder possesses high-temperature and salt tolerance, making it widely applicable.

[0035] Example 9: The retarder for high-temperature resistant and high-strength cement slurry comprises raw materials including a five-component copolymer retarder, sodium borate, and sodium tripolyphosphate in a mass ratio of 10:1:0.7. The five-component copolymer retarder comprises, by weight, 25 parts of 2-acrylamido-2-methylpropanesulfonic acid, 20 parts of acrylic acid, 20 parts of sodium styrenesulfonate, 5 parts of vinyl pyrrolidone, and 7 parts of acrylic acid phosphate. The retarder is obtained by the following method: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution to 6 with an 8% by mass concentration sodium hydroxide solution; wherein the mass concentration of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution is 12%; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution at 30°C until it is completely dissolved, and then adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and causing a polymerization reaction for 5 hours to obtain a viscous liquid; wherein the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of 1:1, the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 3%, and the amount of the initiator solution added is 20% of the weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and carry out a chelation reaction at 60° C. for 5 hours to obtain a viscous solution. The viscous solution is purified again, dried and crushed, and dissolved in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry with a mass concentration of 40%.

[0036] Example 10: The retarder for high-temperature resistant and high-strength cement slurry comprises raw materials including a five-component copolymer retarder, sodium borate, and sodium tripolyphosphate in a mass ratio of 10:2:1.0. The five-component copolymer retarder comprises, by weight, 35 parts of 2-acrylamido-2-methylpropanesulfonic acid, 30 parts of acrylic acid, 30 parts of sodium styrenesulfonate, 8 parts of vinyl pyrrolidone, and 10 parts of acrylic acid phosphate. The retarder is obtained by the following method: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution to 6 with a 12% mass concentration of sodium hydroxide solution; wherein the mass concentration of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution is 18%; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution at 35°C until it is completely dissolved, and then adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and causing a polymerization reaction for 5 hours to obtain a viscous liquid; wherein the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of 1.5:1, the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 5%, and the amount of the initiator solution added is 24% of the weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and carry out a chelation reaction at 70°C for 4 hours to obtain a viscous solution. The viscous solution is purified again, dried and crushed, and dissolved in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry with a mass concentration of 40%.

[0037] Example 11: The retarder for high-temperature resistant and high-strength cement slurry comprises raw materials including a five-component copolymer retarder, sodium borate, and sodium tripolyphosphate in a mass ratio of 10:1.5:0.7. The five-component copolymer retarder comprises, by weight, 30 parts of 2-acrylamido-2-methylpropanesulfonic acid, 25 parts of acrylic acid, 25 parts of sodium styrenesulfonate, 7 parts of vinyl pyrrolidone, and 8 parts of acrylic acid phosphate. The retarder is obtained by the following method: S1, adding the required amounts of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate to deionized water and stirring uniformly to obtain a mixed solution, and adjusting the pH of the mixed solution to 5.5 with a 10% by mass concentration sodium hydroxide solution; wherein the mass concentration of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution is 16%; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution at 40°C until it is completely dissolved, and then adding a required amount of initiator solution dropwise to the mixed solution, heating and refluxing, and causing a polymerization reaction for 7 hours to obtain a viscous liquid; wherein the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of 1.2:1, the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 4%, and the amount of the initiator solution added is 20% of the weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4. Add the required amounts of pentapolymer retarder, sodium borate and sodium tripolyphosphate to deionized water in sequence and mix well to obtain a mixture. Place the mixture in a nitrogen atmosphere and carry out a chelation reaction at 65° C. for 4 hours to obtain a viscous solution. The viscous solution is purified again, dried and crushed, and dissolved in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry with a mass concentration of 40%.

[0038] Compared with the prior art, the present invention has the following beneficial effects: First, the retarder for high-temperature resistant and high-strength cement slurry of the present invention overcomes the limitations of conventional polymer retarders in terms of the limited type and quantity of comonomers. It is obtained by mixing a preferred pentapolymer retarder with an inorganic high-temperature resistant retarder (inorganic salt sodium borate) in a certain proportion at room temperature, and then adding a chelating agent, sodium tripolyphosphate, for a chelating reaction. This retarder combines the advantages of polymer retarders and inorganic salt retarders, while avoiding the disadvantages of using either alone. It organically combines the advantages of single temperature resistance and a wide temperature applicability range with the promotion of early strength on high-rise surfaces with large temperature differences. This not only meets the high-temperature resistance technical requirements for ultra-deep well cementing, but also solves the problem of difficulty in achieving early strength on high-rise surfaces with large temperature differences. Secondly, the molecular design of the retarder for high-temperature resistant and high-strength cement slurry of the present invention introduces a five-membered copolymer retarder. In the molecular structure design of the five-membered copolymer retarder, the main chain is a sulfonic acid functional group (2-acrylamido-2-methylpropanesulfonic acid), which improves the rigidity of the molecular chain and enhances the stability and salt resistance of the molecular main chain; the introduction of a vinyl monomer with a carboxylic acid group (sodium styrene sulfonate) further enhances the adsorption capacity on the cement surface, prevents the hydration of cement particles and achieves a retarding effect; the introduction of a carboxylic acid group (acrylic acid) and the Ca in the cement slurry 2+ Chelate, delay Ca 2+ The concentration reaches supersaturation, enhancing high-temperature resistance and better meeting high-temperature resistance requirements. A pentacyclic lactam compound (N-vinylpyrrolidone) grafted onto the side chain improves side chain rigidity, further stabilizes the molecular structure, and prevents molecular chain breakage at high temperatures, further enhancing the polymer's high-temperature resistance. This invention utilizes a pentapolymer retarder with excellent retarding effect and high-temperature resistance as raw material to produce a high-performance, high-temperature-resistant, high-strength cement slurry retarder, solving the problem of rapid hydration of cement slurry at high temperatures. Third, the retarder for high-temperature resistant and high-strength cement slurry of the present invention adopts a free radical aqueous solution polymerization process, and the initiator is selected from inorganic peroxides, specifically a mixed solution of ammonium persulfate and potassium bisulfite in a certain proportion. This makes the conversion rate of the synthesized retarder for high-temperature resistant and high-strength cement slurry of the present invention high, and the operation process is simple and easy; Fourth, in order to solve the problem of high-temperature strong dispersibility of existing high-temperature resistant retarders, the present invention introduces a five-membered heterocyclic lactam compound (N-vinylpyrrolidone) into the molecular chain, which can improve the rigidity of the molecular chain. Part of it undergoes self-polymerization reaction, and part of it generates a viscous colloidal substance, which increases the consistency of the cement slurry, improves the high-temperature strong dispersibility, and improves the "bulging" and "core-wrapping" phenomena of the cement slurry under high-temperature conditions. At the same time, part of the monomers containing a single carboxyl group is used to replace the monomers containing a double carboxyl group, and acrylic acid is introduced, which further reduces the high-temperature dispersibility of the retarder for high-temperature resistant and high-strength cement slurry of the present invention, and solves the problem of high-temperature cement slurry sedimentation.

[0039] Fifth, the retarder for high-temperature resistant and high-strength cement slurry of the present invention has an appropriate molecular weight, is easily soluble in water, has a good linear relationship, is not sensitive to dosage or temperature, and is more operable for on-site operations.

[0040] Sixth, the retarder for high-temperature resistant and high-strength cement slurry of the present invention contains a small amount of inorganic salt retarder, which reacts with calcium ions in the cement slurry under medium and low temperature conditions to effectively delay the hydration process of the cement, ensuring a retarding effect at medium and low temperatures. For normal cementing operations, it ensures that there is no temperature inversion in the thickening experiment, that is, there will be no phenomenon of long thickening time at high temperature and short thickening time at low temperature, providing a guarantee for safe cementing operations.

[0041] Seventh, the pentapolymer retarder obtained by polymerization reaction and purification of the present invention is finally chelated again with sodium borate and chelating agent sodium tripolyphosphate in an oxygen-free nitrogen atmosphere of 45°C to 70°C, and purified again, thereby avoiding the dislocation of the retarding functional groups, reducing impurities, and increasing the effective components of the high-temperature resistant retarder.

[0042] Example 12: The retarder for high-temperature resistant and high-strength cement slurry is obtained by the following method: S1, adding an appropriate amount of deionized water to a four-necked flask reaction apparatus equipped with a reflux condenser, a thermometer, and a stirrer, and fixing the apparatus in a constant temperature water bath, respectively weighing 25 parts of 2-acrylamido-2-methylpropanesulfonic acid, 20 parts of acrylic acid, 35 parts of sodium styrenesulfonate, 8 parts of N-vinyl pyrrolidone, and 12 parts of acrylic acid phosphate, placing them in the four-necked flask reaction apparatus and stirring them uniformly to obtain a mixed solution such that the total mass concentration of the solute in the mixed solution is 18%, and adding dropwise an 8% mass concentration of sodium hydroxide solution to adjust the pH value of the mixed solution to 5; S2, adjusting the temperature of the constant temperature water bath to 45°C, introducing inert nitrogen gas into the four-necked flask reaction device, removing oxygen from the device, stirring at a low speed of 600 rpm to completely dissolve the mixed solution, then adding an initiator solution dropwise to the device, heating and reflux, and reacting at a constant temperature for 6 hours to obtain a viscous liquid; wherein the initiator solution is a mixed aqueous solution of ammonium persulfate and potassium bisulfite in a mass ratio of 1.2:1, the mass concentration of the solutes (ammonium persulfate and potassium bisulfite) in the initiator solution is 3%, and the amount of the initiator solution added is 20% of the weight of the solutes (2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, vinyl pyrrolidone, and acrylic acid phosphate) in the mixed solution; S3, cooling the viscous liquid to room temperature, purifying, drying and crushing to obtain a pentapolymer retarder; S4, uniformly mixing the pentapolymer retarder, sodium borate and sodium tripolyphosphate in a mass ratio of 10:1.5:0.7, and dissolving them in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry with a mass concentration of 40%.

[0043] In Example 12 of the present invention, the weight-average molecular weight of the pentapolymer retarder is 28,000. Its molecular structure comprises a main chain composed of three monomers: 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, and sodium styrenesulfonate, with N-vinyl pyrrolidone monomers and acrylic acid phosphate monomers grafted onto both ends of the main chain.

[0044] Example 13: The difference from Example 12 of the present invention is that in step S1, the material ratio is changed to "weigh 30 parts of 2-acrylamido-2-methylpropanesulfonic acid, 25 parts of acrylic acid, 30 parts of sodium styrenesulfonate, 10 parts of N-vinyl pyrrolidone, and 7 parts of acrylic acid phosphate", and the remaining steps are the same as Example 12.

[0045] In Example 13 of the present invention, the weight-average molecular weight of the pentapolymer retarder is 36000. The main chain of its molecular structure is composed of four monomers: 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, and acrylic acid phosphate, with N-vinyl pyrrolidone monomer grafted onto the acrylic acid side chain.

[0046] Example 14: The difference from Example 12 of the present invention is that in step S1, the material ratio is changed to "22 parts of 2-acrylamido-2-methylpropanesulfonic acid, 16 parts of acrylic acid, 20 parts of sodium styrenesulfonate, 19 parts of N-vinyl pyrrolidone, and 23 parts of acrylic acid phosphate", and the remaining steps are the same as Example 12.

[0047] In Example 14 of the present invention, the weight average molecular weight of the pentapolymer retarder is 15000. The main chain of its molecular structure is composed of five monomers: 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrenesulfonate, acrylic acid phosphate, and N-vinyl pyrrolidone.

[0048] Example 15: Cement slurries were prepared using the retarder for high-temperature resistant and high-strength cement slurry prepared in Examples 12 to 14 of the present invention as one of the raw materials, and were respectively recorded as cement slurries A, B and C. The thickening time of each cement slurry was tested at a temperature of 150°C to 220°C, a pressure of 180 MPa, and a heating time of 110 min.

[0049] Cement slurry formula: Cement slurry A: 100 parts of Shawan G grade cement + 40 parts of quartz sand + 1.5 parts of dispersant + 8 parts of microsilica + 6 parts of fluid loss additive + 4 parts of retarder for high-temperature resistant and high-strength cement slurry obtained in Example 12 of the present invention + 52 parts of water.

[0050] Cement slurry B: 100 parts of Shawan G grade cement + 40 parts of quartz sand + 1.5 parts of dispersant + 8 parts of microsilica + 6 parts of fluid loss additive + 6 parts of retarder for high-temperature resistant and high-strength cement slurry obtained in Example 13 of the present invention + 50 parts of water.

[0051] Cement slurry C: 100 parts of Shawan G grade cement + 40 parts of quartz sand + 1.5 parts of dispersant + 8 parts of microsilica + 6 parts of fluid loss additive + 8 parts of retarder for high-temperature resistant and high-strength cement slurry obtained in Example 14 of the present invention + 48 parts of water.

[0052] The test results of the thickening time of each cement slurry, such as Figure 1 As shown, from Figure 1 It can be seen that the higher the temperature, the shorter the thickening time of each cement slurry; the lower the temperature, the longer the thickening time of each cement slurry, meeting the requirement of a 220°C anti-cycling temperature. Moreover, when the temperature changes by 10°C, the thickening time changes by less than 40%, indicating that the cement slurry obtained using the retarder for high-temperature-resistant, high-strength cement slurry of the present invention as raw material is not temperature sensitive.

[0053] Example 16: Cement slurry B was prepared using the retarder for high-temperature-resistant, high-strength cement slurry prepared in Example 13 as one of the raw materials. The formulation is as described in Example 15. After curing Cement slurry B for 24 hours at different bottomhole static temperatures (pressure 21 MPa, temperature 200°C to 230°C), cement paste was obtained and its compressive strength was tested. Test conditions: a cycle coefficient of 0.9 and a thickening time of 320 to 350 minutes for Cement slurry B. The compressive strength of the cement paste was also tested at tophole temperatures of 90°C, 100°C, and 110°C, respectively.

[0054] The test results, shown in Table 1, show that the cement developed strength rapidly and achieved high compressive strength at various bottomhole static temperatures above 200°C. Under conditions of a large temperature gradient of 140°C or higher, the cement developed excellent early strength at the return surface, with a minimum compressive strength of 7.9 MPa after 48 hours and exceeding 14 MPa after 72 hours. This effectively meets the technical requirements for high-temperature-difference cementing in ultra-deep wells with long, single-stage cementing sections.

[0055] Example 17: Cement slurry B was prepared using the retarder for high-temperature resistant and high-strength cement slurry prepared in Example 13 of the present invention as one of the raw materials. The formula is shown in Example 15. The cement slurry B was subjected to a thickening time test under high temperature and high pressure (temperature of 220°C and pressure of 180 MPa).

[0056] The test results are as follows Figure 2 As shown by Figure 2 It can be seen that the retarder for high-temperature resistant and high-strength cement slurry of the present invention has strong high-temperature resistance and a straight and stable thickening curve, indicating that the retarder for high-temperature resistant and high-strength cement slurry of the present invention has no high-temperature shear dilution phenomenon under high-temperature conditions, good high-temperature stability, no "bulging" or "coring" phenomenon, and a thickening time of 420 minutes, which meets the technical requirements of ultra-deep well cementing.

[0057] In summary, the retarder for high-temperature resistant and high-strength cement slurry of the present invention can not only significantly prolong the thickening time of cement slurry under high temperature and high pressure conditions, but also enable the cement slurry to maintain good sedimentation stability, thereby solving the problem that the existing retarder easily causes poor high-temperature sedimentation stability of cement slurry.

[0058] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or removed according to actual needs to meet the requirements of different situations.

Claims

1. A retarder for high temperature resistant and high strength cement slurry, characterized in that The raw materials include a five-polymer retarder, sodium borate and sodium tripolyphosphate in a mass ratio of 10:1 to 2:0.6 to 1.

1. The raw materials of the five-polymer retarder include, by weight, 25 to 35 parts of 2-acrylamido-2-methylpropane sulfonic acid, 20 to 30 parts of acrylic acid, 20 to 30 parts of sodium styrene sulfonate, 5 to 8 parts of vinyl pyrrolidone and 7 to 10 parts of acrylic acid phosphate.

2. The retarder for high temperature resistant and high strength cement slurry according to claim 1, characterized in that Obtained as follows: S1, adding the required amount of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone and acrylic acid phosphate into deionized water and stirring to obtain a mixed solution, and adjusting the pH of the mixed solution; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution until it is completely dissolved, and then dropping a required amount of initiator solution into the mixed solution, heating and refluxing, and obtaining a viscous liquid after a polymerization reaction occurs; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4, sequentially adding required amounts of a pentapolymer retarder, sodium borate and sodium tripolyphosphate into deionized water and mixing well to obtain a mixture, placing the mixture in a nitrogen atmosphere and performing a chelating reaction to obtain a viscous solution, and again purifying, drying and crushing the viscous solution, and dissolving it in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry.

3. The retarder for high temperature resistant and high strength cement slurry according to claim 2, characterized in that In step S1, the mass concentration of the solute in the mixed solution is 12% to 18%.

4. The retarder for high temperature resistant and high strength cement slurry according to claims 2 to 3, characterized in that In step S1, the pH of the mixed solution is adjusted to 4 to 8 by using a sodium hydroxide solution with a mass concentration of 8% to 12%.

5. The retarder for high temperature resistant and high strength cement slurry according to any one of claims 2 to 4, characterized in that In step S2, the initiator solution is prepared by mixing ammonium persulfate and potassium bisulfite in a mass ratio of 1 to 1.5:1, and the mass concentration of the solute in the initiator solution is 3% to 5%.

6. The retarder for high temperature resistant and high strength cement slurry according to any one of claims 2 to 5, characterized in that In step S2, the amount of the initiator solution added is 12% to 40% of the weight of the solute in the mixed solution.

7. The retarder for high temperature resistant and high strength cement slurry according to any one of claims 2 to 6, characterized in that In step S2, the stirring temperature is 30°C to 50°C, and the polymerization reaction time is 5h to 8h. In step S4, the chelation reaction is performed at a temperature of 45°C to 70°C, and the time is 4h to 6h.

8. The retarder for high temperature resistant and high strength cement slurry according to any one of claims 2 to 7, characterized in that The mass concentration of the solute in the retarder for high temperature resistant and high strength cement slurry is 30% to 45%.

9. A method for preparing a retarder for high temperature resistant and high strength cement slurry according to any one of claims 1, 3 to 8, characterized in that Proceed as follows: S1, adding the required amount of 2-acrylamido-2-methylpropanesulfonic acid, acrylic acid, sodium styrene sulfonate, vinyl pyrrolidone and acrylic acid phosphate into deionized water and stirring to obtain a mixed solution, and adjusting the pH of the mixed solution; S2, isolating the mixed solution from oxygen and placing it in a nitrogen atmosphere, stirring the mixed solution until it is completely dissolved, and then dropping a required amount of initiator solution into the mixed solution, heating and refluxing, and obtaining a viscous liquid after a polymerization reaction occurs; S3, cooling the viscous liquid to room temperature, and then purifying, drying and crushing in sequence to obtain a pentapolymer retarder; S4, sequentially adding required amounts of a pentapolymer retarder, sodium borate and sodium tripolyphosphate into deionized water and mixing well to obtain a mixture, placing the mixture in a nitrogen atmosphere and performing a chelating reaction to obtain a viscous solution, and again purifying, drying and crushing the viscous solution, and dissolving it in deionized water to obtain a retarder for high-temperature resistant and high-strength cement slurry.

Citation Information

Patent Citations

  • High-temperature-resistant copolymer oil well cement retarder and preparation method thereof

    CN104403056A

  • High-inhibitive medium-high-temperature oil well cement retarder and preparation method thereof

    CN106008844A

  • Retarder for high-temperature-resistant cement paste system

    CN107418534A